ANALISIS SISTEM PENGENDALIAN INTERN PENJUALALN PRODUK ELELTRONIK PT. MATAHARI PUTRA PRIMA Tbk - Rifani Akbar Sulbahri; Yessi Nelissma Fitri (Jurnal RATRI (Riset Akuntansi Tridinanti), 2019)
ABSTRACT            The increasing sales demand in the market makes the company management must create a good sales structure with sales progress as an evaluation of activities in order to support and analyze the implementation of an internal control system of electronic product sales at PT. Matahari Putra Prima Tbk. While the method of discussion of this study uses qualitative and quantitative analysis methods.            The results of this study are seen from all elements of sales internal control conducted by PT. Matahari Putra Prima Tbk, showing effective / appropriate results. But in the division of tasks and authority in the company there are work traps that can hamper the company's performance. If in the division of tasks and authority in the company there is a double job this can hamper the company's performance, the company should divide the tasks and authority according to their respective functions.Keywords: sales, internal control